1999
DOI: 10.1093/jjco/29.11.550
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Markers CEA, CA19-9 and CA125 in Monitoring of Response to Systemic Chemotherapy in Patients with Advanced Gastric Cancer

Abstract: The measurement of tumor markers might be useful in monitoring response and in predicting the prognosis of patients with advanced gastric cancer treated with systemic chemotherapy. Tumor markers may be used as a means of monitoring treatment in patients when in an imaging study it is difficult to assess response to chemotherapy in clinical practice. Further studies are required to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 12 publications
2
44
0
Order By: Relevance
“…The reported doubling time estimate, based on the serum level of CEA, agreed with the actual tumor doubling time in 112 previously untreated patients with recurrent gastric cancers [66]. The CEA doubling time ranged from 12 to 105 days, with a mean of 37.5 days.…”
Section: Doubling Time and Lead Time Of Elevated Serum Markerssupporting
confidence: 67%
See 1 more Smart Citation
“…The reported doubling time estimate, based on the serum level of CEA, agreed with the actual tumor doubling time in 112 previously untreated patients with recurrent gastric cancers [66]. The CEA doubling time ranged from 12 to 105 days, with a mean of 37.5 days.…”
Section: Doubling Time and Lead Time Of Elevated Serum Markerssupporting
confidence: 67%
“…Yamao et al [66] monitored changing patterns in CEA, CA19-9, and CA125 levels during systemic chemotherapy to determine the relationship between changes in the serum tumor marker levels and the response assessment in imaging studies throughout the treatment course. The sensitivity and negative predictive value of falling tumor marker levels after chemotherapy for a partial response in imaging was 100 %.…”
Section: Clinical Significance Of Serum Marker Monitoring During Chemmentioning
confidence: 99%
“…Yamao et al [6] reported that, in 26 patients with advanced gastric cancer, the survival time of responders assessed by the 4 tumor markers CEA, CA19-9, CA125, and CA72-4 was significantly longer than that of non-responders. In our study, the CA125 response showed an excellent correlation with the reduction of ascites and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the 2 common markers CEA and CA19-9, CA125 and CA72-4 have been reported to be elevated in advanced gastric cancer [6]. However, these markers are not all commonly measured, due to the lack of clinical evidence of their value.…”
Section: Introductionmentioning
confidence: 99%
“…The use of tumor markers has become a very attractive method for the detection and diagnosis of neoplastic diseases, as well as for the monitoring of their course after radical surgery or during chemotherapy 18,19 . One of the challenging problems in the diagnosis and postoperative follow-up of patients with gastric cancer is the low sensitivity of the tumor markers that are currently being used 8 .…”
Section: Discussionmentioning
confidence: 99%